Violence, Cruelty, Power: Reflections on Heteronomy - Rundell, John (Cosmos and History: The Journal of Natural and Social Philosophy, 2012)
<!-- /* Font Definitions */ @font-face {font-family:"Palatino Linotype"; panose-1:2 4 5 2 5 5 5 3 3 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-536870265 1073741843 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Palatino Linotype"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page WordSection1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> There is an opening in Castoriadis' work for a notion of cruelty, and it emerges in the way in which he develops his idea of heteronomy, as a human world that is blinded or deflected away from human self-creation. This essay is an attempt to locate cruelty constitutively or ontologically in a post-metaphysical register, as an act of creativity that can be given form as a very particular act of singularity, that is, without regard for the other. Acts of human cruelty are acts of imaginary, creative activity among others that themselves are form, that is, expressed in physically embodied, objectivated, linguistic or symbolic form, and often become highly stylized, and when socially instituted, have their own spatial and temporal dimensions. In this way, it is distinct from relations of power.